THE PHONOLOGICAL OF BATAKNESE LANGUAGE OF BASIC ENGLISH LEARNER - Ruth Wahyu Ningsih Hutasoit; Indah Arvianti (Jurnal CULTURE (Culture, Language, and Literature Review), 2020)
Most Indonesian people master at least two languages, Bahasa Indonesia and mother tongue. Both of them can give impact into the phenomena of language, like code mixing, interference, and etc. Linguistics is divided into two parts those are micro linguistic and macro linguistics. Micro linguistics, the sub-discipline linguistics; consist of phonology and phonetic, morphology, syntax, and semantics. While macro linguistic consists of: psycholinguistic, anthropolinguistics and sociolinguistic. In this research, the writer analyzes about The interference of Bataknese language in spoken English of beginner. The data which are used are primary and secondary sources. The method of data collection are metode simak, and metode simak bebas libat cakap. To analyze the data, the writer uses metode padan and metode agih. The method of data presentation use formal method and informal method. Interference of language is a form of irregularities in the use of language of the norms that exist as a result of language contact or the introduction of more than one language is used interchangeably by the speakers.The result of the research shows that Bataknese students heads towards their mother tongue, so when they speak English, there are some interferences of Bataknese to English especially in phonology. In phonology there are two elements, those are Segmental and Suprasegmental. For the Segmentel element, there are vowel and consonant change of Bataknese to English. In Suprasegmental, there are intonation and stress interference of Bataknese and English.